2016
DOI: 10.21157/j.ked.hewan.v10i2.5092
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN EKSTRAK BUAH MENGKUDU (Morinda citrifolia) DALAM LARUTAN NATRIUM KLORIDA FISIOLOGIS SEBAGAI BAHAN PENGENCER SEMEN TERHADAP PENINGKATAN KUALITAS SPERMATOZOA AYAM BURAS PADA SUHU RUANG (Effect of Noni Extract Fruit (Morinda citrifolia) in Physiological Saline Solution as Diluent on the Native Chicken Spermatozoa Quality at Room Temperature)

Abstract: The purpose of this research was to analyse the quality and storability of native chicken semen at room temperature after diluted with physiological saline solution (NaCl) supplemented with noni fruit extract. Research methodology used was nested randomized design which variables observed covering the quality of chicken spermatozoa macroscopically and microscopically with the doses of noni fruit extract of 0 % (P0), 10 % (P1), 20 % (P2), and 30 % (P3). Rate of spermatozoa motility at 0, 1, 2, and 3 hours on P0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…The motility of spermatozoa in this study is higher than that reported by Tethool et al (2017), i.e., 68.13%, also higher than Lubis (2011), Danang (2012) and Wiyanti et al (2013) which only get 77% motility. But it is almost the same as the one obtained by Indrawati, Bebas, & Trilaksana, (2013) and Murcahyana et al (2016) which earned 89% and 83.7% respectively. Viability (percentage of life) of spermatozoa of Chicken Kampong obtained at the research is very high (99.73 ± 0.13%) Compared with previous analysis of 79.94% (Tethool et al, 2017), 83.87% (Lubis, 2011), 85.3% (Murcahyana et al, 2016) and 92% (Danang, 2012;Wiyanti et al, 2013;Indrawati et al, 2013).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The motility of spermatozoa in this study is higher than that reported by Tethool et al (2017), i.e., 68.13%, also higher than Lubis (2011), Danang (2012) and Wiyanti et al (2013) which only get 77% motility. But it is almost the same as the one obtained by Indrawati, Bebas, & Trilaksana, (2013) and Murcahyana et al (2016) which earned 89% and 83.7% respectively. Viability (percentage of life) of spermatozoa of Chicken Kampong obtained at the research is very high (99.73 ± 0.13%) Compared with previous analysis of 79.94% (Tethool et al, 2017), 83.87% (Lubis, 2011), 85.3% (Murcahyana et al, 2016) and 92% (Danang, 2012;Wiyanti et al, 2013;Indrawati et al, 2013).…”
Section: Resultssupporting
confidence: 83%
“…Characteristics of fresh Semen chicken Village The results showed that the volume rate of Semen produced was 0.09 ± 0.02 ml/ejaculate, and the pH of Semen 7 (neutral), thick and white in milk. Previous research found that the volume of Semen chickens 0.19 ml (Murcahyana, Susilawati, & Isnaini, 2016) and 0.27 ml (Rahayu, Aji, Nurkhaffah, Fauziyah, & Annisa, 2017). Age and climate factors can cause a low amount of Semen in this research.…”
Section: Resultsmentioning
confidence: 96%
“…Viabilitas semen ayam berbeda-beda bergantung rumpun ayam dan teknik pewarnaan yang digunakan. Nilai viabilitas spermatozoa ayam kampung 85.30±9.09% (Murcahyana et al, 2016), ayam sentul 90.64±1.21%, ayam pelung 89.17±1.23% (Junaedi & Husnaeni, 2019) dan ayam kedu 86.99±2.14% (Saleh et al, 2017 Konsentrasi spermatozoa ayam sebetulnya lebih tinggi dibandingkan dengan ternak lain. Tingginya konsentrasi spermatozoa ayam akibat tidak terdapatnya plasma semen seperti yang dimiliki ternak lain, sebagai contoh pada ayam kampung bisa mencapai 3130±290.30 x10 6 (Danang et al, 2012).…”
Section: Pembahasanunclassified